PENERAPAN SERTIFIKASI HALAL DAN DAMPAKNYA TERHADAP PENJUALAN PRODUK PADA TOKO ROTI DI KABUPATEN BANYUMAS JAWA TENGAH - Rizkiana, Triani; Istianah, Istianah; Fakhrul Muttaqin, Imbatsani (Universitas Islam Negeri Raden Intan Lampung, 2025)
The bakery business in Banyumas Regency is quickly growing in line with the increasing public interest in bread and cake products. Seeing as most people in Banyumas Regency are Muslim, halal certification is a really important thing to keep people’s trust and increase sales. Since 2019, halal certification has become mandatory for every business worker, including bakery businesses. Mostly, every bakery that has obtained halal certification must consistently implement the Halal Product Assurance System (SJPH) to ensure the sustainability of its halal status. In reality, many bakeries in Banyumas Regency that have obtained halal certification still aspect challenges in implementing the SJPH. This study aims to analyze the implementation of halal certification in bakeries in Banyumas Regency and its impact on product sales. This study uses a descriptive qualitative approach with interviews, observations, and documentation at the research locations, Mumtaza Cake and Bakery and Shiawasena Pan BakeHouse. The study found that the halal certification in both bakeries was based on regulatory requirements and the owners’ awareness. The implementation followed SJPH principles, including commitment, raw materials, halal production processes, product handling, monitoring, and evaluation. This consistent application positively impacted sales stability, production, and consumer trust